Integrating technology across the curriculum a database of strategies and lesson plans - Roblyer, M.D. (Columbus : Prentice Hall, 1999)
CD-ROM database of 250 + lesson plans that demonstrate how to effectively integrate technology into K-12 curriculum
System requirements: 386 intel compatible PC, Windows 3.1 or newer (if running Windows 3.1 you must have Win32s 1.30c installed, included on CD), 8 MB RAM (16 MB recommended), 16 colour VGA monitor, CD-ROM
Keywords: Educational innovations; Educational technology; Teaching -- Aids and devices; Information display systems